A reforming hydrogen production catalyst and its preparation method and application
By introducing Cu-Ce solid solution and MgO-Al2O3 composite support into the copper-based catalyst and using polymer surfactants to form a specific pore structure, the shortcomings of copper-based catalysts in low-temperature activity and high-temperature stability are solved, and high-efficiency Methanol water vapor reforming to produce hydrogen.
Patent Information
- Application Number
- CN202411015391.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-26
AI Technical Summary
The existing copper-based catalysts have shortcomings in low-temperature activity and high-temperature stability, resulting in poor performance in methanol water vapor reforming hydrogen production reaction.
By combining Cu-Ce solid solution with MgO-Al2O3 composite support, a specific pore structure was formed during the calcination process by combining the polymer surfactant, inhibiting copper grain growth and improving the activity and stability of the catalyst.
The hydrogen production rate, methanol conversion rate and heat resistance of the catalyst are significantly improved, the CO selectivity is reduced, and the overall performance and stability of the catalyst are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of methanol reforming hydrogen production catalysts and relates to a methanol reforming hydrogen production catalyst supported by a composite carrier and a preparation method and application thereof. Background Art
[0002] Hydrogen has attracted much attention as an energy carrier, especially as a fuel supply for proton exchange membrane fuel cells (PEMFC). Due to certain limitations in the storage and transportation of hydrogen, on-board in-situ alcohol steam reforming hydrogen production technology has attracted people's attention and has potential research and development prospects. Methanol, as a liquid hydrogen storage fuel, has a high H / C ratio and a low conversion temperature. The development of efficient catalysts is the key to realizing methanol steam reforming hydrogen production technology. In the methanol steam reforming hydrogen production reaction (MSR), Cu-based catalysts are an extremely important type of catalyst in the field of methanol steam reforming hydrogen production because of their high activity, low CO selectivity, and low price. Commercial catalysts are mainly CuO / ZnO / Al 2 O 3 However, due to the low melting point of copper metal, copper grains are more likely to aggregate and grow and become inactive than other metal particles. Therefore, how to further improve the low-temperature activity and high-temperature stability of copper-based catalysts is the key to improving the comprehensive performance and market competitiveness of copper-based catalysts.
[0003] The carrier of copper-based catalyst has an important influence on the activity and stability of the catalyst. Commonly used carriers include silica, alumina, biochar, etc. In recent years, composite carriers have been widely used in copper-based catalysts. The present invention uses MgO-Al 2 O 3 As a composite support for copper-based catalysts, Al 2 O 3 Good thermal stability can ensure the stability of the catalyst under high temperature reaction conditions. The MgO carrier has a large surface area, stable chemical properties, and good anti-sintering performance. The prepared catalyst has high activity and selectivity. 2 O 3 Composite carrier, taking into account the MgO carrier and its Al 2 O 3 Due to the characteristics of the carrier, the prepared copper-based catalyst has higher activity, selectivity and stability. Summary of the invention
[0004] The present invention utilizes the property that copper ions and cerium metal with similar ion radius can form a solid solution, and through the confinement effect of the crystal structure, the copper ions are confined inside the crystal lattice, and the growth of copper grains during use is suppressed. In addition, the present invention is combined with a composite carrier with stable performance, which is conducive to the loading of catalyst active components on the surface of the composite carrier, thereby improving the hydrogen production rate of the catalyst and the conversion rate of methanol, and has low selectivity for CO. The composite carrier can prevent the catalyst from sintering and deactivation, and improves the stability of the catalyst.
[0005] The present invention adopts polymer surfactant to prepare MgO-Al 2 O 3 The composite carrier uses a polymer surfactant to adsorb on the surface of the magnesium source and the aluminum source, which slows down the aggregation of magnesium oxide or aluminum oxide during the calcination process and is conducive to the calcination to form MgO-Al with specific pores. 2 O 3 The composite carrier improves the catalytic activity and methanol conversion rate of the copper-based catalyst and improves the CO selectivity and heat resistance.
[0006] The present invention provides a crystal confined catalyst for methanol reforming to produce hydrogen, the crystal confined catalyst comprising a catalyst precursor and MgO-Al 2 O 3 Composite carrier.
[0007] The catalyst precursor includes a Cu-Ce solid solution, wherein the Cu ions are present in CeO 2 In the lattice.
[0008] The present invention also provides a method for preparing a reforming hydrogen production catalyst, comprising the following steps:
[0009] 1) Mix copper salt, cerium salt and water evenly, add precipitant until pH>8.0, heat and stir. Stirring, standing and aging to obtain a precipitate suspension; wherein the mass ratio of the copper salt to the cerium salt is 1-5:10-20;
[0010] 2) washing and filtering the precipitated suspension in step 1) or centrifuging and washing it, and drying it to obtain a copper-cerium mixed precursor;
[0011] 3) dissolving a modifier in water, impregnating the mixed precursor of step 2), and drying to obtain a catalyst precursor; the modifier is selected from chlorides or nitrates of metal ions such as Pt, Pd, Ru, La, Sm, Co, Ni, and Zr; the mass fraction of the modifier is 0.1% to 15% of the total mass of the copper salt and the cerium salt;
[0012] 4) mixing the catalyst precursor of step 3) with the composite carrier in a mass ratio of 1:1-2, and then transferring the mixture into a tank for ball milling to obtain a ball milling product;
[0013] 5) calcining the product after ball milling in step 4) at 200-500° C. for 1-5 h, and then adding graphite to form a finished catalyst;
[0014] The preparation method of the composite carrier comprises the following steps:
[0015] S1. Mix a magnesium source and an aluminum source in a mass ratio of 1:0.5-4, disperse the mixture in water, add a polymer surfactant, and stir to obtain a mixed solution; the polymer surfactant comprises at least one of polyvinyl alcohol, polyacrylamide, sodium polystyrene sulfonate, and lignin sulfonate; the mass fraction of the polymer surfactant is 1-30% of the total amount of the magnesium source and the aluminum source;
[0016] S2, adding ammonia water to the mixed solution of S1 until the pH value of the solution is 9-10, continuing to stir for a reaction time, standing, filtering, washing, and drying to obtain a carrier intermediate product;
[0017] S3, calcining the carrier intermediate product of step S2 in nitrogen or air at 450-700°C for 2-4h to obtain MgO-Al 2 O 3 Composite carrier.
[0018] In the step 1), the copper salt includes at least one of copper nitrate, copper acetate and copper chloride; the cerium salt includes at least one of cerium nitrate and cerium chloride.
[0019] In the step 1), the precipitant is at least one of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate.
[0020] In the step 1), the heating temperature is 50-80° C., the stirring time is 1-5 hours, and the standing aging time is 2-6 hours.
[0021] The ball milling includes dry ball milling or wet ball milling, and the ball milling time is 0.5 to 5 hours; the medium of the wet ball milling includes at least one of water, anhydrous ethanol, glycerol, and isopropanol.
[0022] In the step S1 of preparing the composite carrier, the magnesium source includes at least one of magnesium chloride, magnesium nitrate, and magnesium acetate; the aluminum source includes at least one of aluminum chloride, aluminum nitrate, and aluminum isopropoxide.
[0023] In the step S2 of preparing the composite carrier, the stirring reaction time is 1 to 3 hours; and the standing time is 2 to 5 hours.
[0024] In the step S2 of preparing the composite carrier, distilled water and / or ethanol are used for washing, and the drying temperature is 90-110° C. for 1-4 hours.
[0025] The present invention also includes a reforming hydrogen production catalyst prepared by the above method.
[0026] The present invention also includes the use of a reforming hydrogen production catalyst in catalyzing methanol reforming hydrogen production. The reaction temperature of the reforming hydrogen production catalyst when catalyzing methanol reforming hydrogen production is 170-350°C.
[0027] The present invention also adds a modifier, which can increase the surface oxygen vacancies and enhance the correlation between the active component and the carrier, and further improve the low-temperature activity of the catalyst. The preferred modifier of the present invention is selected from the chloride or nitrate of the metal ion Pt, Pd, Ru, La, Sm, Co, Ni, and Zr; the mass fraction of the modifier is 0.1% to 15% of the total mass of the copper salt and the cerium salt; during the use of the modifier, it is first dissolved in an appropriate amount of water, and then mixed and impregnated with the copper-cerium mixed precursor. The concentration of the modifier aqueous solution is not specifically required, as long as the modifier and the copper-cerium mixed precursor can be mixed evenly.
[0028] The inventors have found that in the process of preparing the composite carrier, the type of surfactant significantly affects the performance of the composite carrier. The present invention preferably uses a polymer surfactant, such as at least one of polyvinyl alcohol, polyacrylamide, sodium polystyrene sulfonate, and lignin sulfonate. When the polymer surfactant is used, during the stirring and mixing process of the magnesium source and the aluminum source, the polymer surfactant will be adsorbed on the surface of magnesium oxide or aluminum oxide, slowing down the aggregation of magnesium oxide or aluminum oxide, which is conducive to the formation of uniformly distributed magnesium oxide and aluminum oxide, and a MgO-Al2O3 with specific pores can be formed during the calcination process. 2 O 3 The composite carrier is beneficial to the loading of the active components of the catalyst and can significantly improve the catalytic activity, methanol conversion rate and heat resistance of the copper-based catalyst.
[0029] The inventors further found that the calcination temperature of the composite carrier is an important parameter affecting the performance of the catalyst carrier. The present invention selects the carrier calcination temperature of 450-700°C and the calcination time of 2-4h. Under the calcination temperature and time conditions, the prepared MgO-Al 2 O 3 The composite carrier is conducive to interacting with the active components and improving the catalytic activity and heat resistance of the copper-based catalyst.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1) The active component of the present invention is a uniform Cu-Ce solid solution, which can synergistically enhance the methanol conversion rate and improve the CO selectivity by combining with the composite carrier.
[0032] 2) The present invention incorporates Cu into CeO 2In the lattice, through the crystal confinement effect, during the catalyst reduction process, the active metal particles can be made smaller and dispersed more evenly, thereby enhancing high-temperature stability.
[0033] 3) The present invention can increase the surface oxygen vacancies and enhance the correlation between the active components and the carrier by adding a modifier, thereby improving the low-temperature activity of the catalyst.
[0034] 4) The present invention uses a polymer surfactant to prepare MgO-Al at a suitable calcination temperature and time. 2 O 3 The composite support has an excellent pore structure, MgO-Al 2 O 3 The composite carrier takes into account the MgO carrier and its Al 2 O 3 The characteristics of the carrier are conducive to the loading of copper-based catalysts. The catalyst can be used in the high temperature range of 170 to 350°C, with high activity, high selectivity and stable catalytic performance.
[0035] 5) The present invention solves the problems of easy sintering at high temperature and poor CO selectivity of existing copper-based catalysts; the preparation method is simple, easy to operate, has low pollution, and is easy to industrialize. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below by specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0037] Example 1
[0038] 1) Accurately weigh 5 g of copper nitrate and 20 g of cerium nitrate and dissolve them in 150 ml of deionized water. After magnetic stirring for 1 h in a constant temperature water bath at 80° C., a transparent solution is obtained. Concentrated ammonia (25-28 wt.%) is added as a precipitant in sequence until the pH of the solution is greater than 8.0 to completely precipitate the metal ions. The solution is magnetically stirred for 1 h in a constant temperature water bath at 80° C., and then aged and allowed to stand for 4 h in a constant temperature water bath at 80° C. to obtain a precipitated suspension;
[0039] 2) The precipitate suspension of step 1) is vacuum filtered, and the solid product is washed with deionized water until the total soluble solid TDS in the filtrate is less than 20 ppm. The precipitate is transferred to an oven and dried at 110° C. for 3 h to obtain a copper-cerium solid powder precursor.
[0040] 3) 2g of lanthanum nitrate [La(NO 3 ) 3 6H 2 O] was dissolved in an appropriate amount of deionized water. The lanthanum nitrate aqueous solution is added dropwise to the copper cerium solid powder in step 2) until it is completely absorbed, and then transferred to an oven and dried at 110° C. for 2 hours to obtain a catalyst precursor.
[0041] 4) Take a certain amount of the above catalyst precursor, mix it with the composite carrier in a mass ratio of 1:1, and then transfer it into a tank and ball mill it for 4 hours to obtain a ball milled product.
[0042] 5) The product after ball milling in step 4) is calcined at 250° C. for 4 hours, and then pressed into graphite to obtain a finished catalyst.
[0043] The preparation method of the composite carrier in this embodiment includes:
[0044] S1. Weigh 30 g of magnesium nitrate and aluminum nitrate, dissolve them in 250 mL of deionized water, stir for 20 min, add 5 g of polyvinyl alcohol, stir and mix at 45 °C for 15 min to obtain a composite precursor solution;
[0045] S2, adding ammonia water to the composite precursor solution of S1 until the pH of the solution is about 9.0, continuing to stir the reaction time for 2 hours, standing for 3 hours, filtering, washing with deionized water twice, and drying at 100°C for 3 hours to obtain a carrier intermediate product;
[0046] S3, then the carrier intermediate product was calcined at 450 ° C for 4 h in a nitrogen atmosphere, crushed and sieved to obtain MgO-Al 2 O 3 Composite carrier.
[0047] Example 2
[0048] 1) Accurately weigh 5 g of copper chloride and 15 g of cerium nitrate and dissolve them in 100 ml of deionized water. After magnetic stirring for 1 h in a constant temperature water bath at 90° C., a transparent solution is obtained. Concentrated ammonia (25-28 wt.%) is added as a precipitant in sequence until the pH of the solution is greater than 8.0 to completely precipitate the metal ions. The solution is magnetically stirred for 2 h in a constant temperature water bath at 85° C., and then aged and allowed to stand for 3 h in a constant temperature water bath at 80° C. to obtain a precipitated suspension;
[0049] 2) The precipitate suspension of step 1) is vacuum filtered, and the solid product is washed with deionized water until the total soluble solid TDS in the filtrate is <20ppm; the precipitate is transferred to an oven and dried at 100°C for 5h to obtain a copper-cerium solid powder precursor.
[0050] 3) 1.5 g zirconium nitrate [Zr(NO 3 ) 4 ] is dissolved in an appropriate amount of deionized water, and the zirconium nitrate aqueous solution is added dropwise to the copper cerium solid powder in step 2) until it is completely absorbed, and then transferred to an oven and dried at 100°C for 3h to obtain a catalyst precursor.
[0051] 4) Take a certain amount of the above catalyst precursor, mix it with the composite carrier in a mass ratio of 1:1.2, and then transfer it into a tank and ball mill it for 2.5 hours to obtain a ball milled product.
[0052] 5) The product after ball milling in step 4) is calcined at 300° C. for 4 hours, and then pressed into a sheet with graphite to obtain a finished catalyst.
[0053] The preparation method of the composite carrier in this embodiment includes:
[0054] S1. Weigh 25 g of magnesium chloride and aluminum chloride, dissolve them in 250 mL of deionized water, stir for 15 min, add 4.5 g of polyacrylamide, and stir and mix at 40 ° C for 20 min to obtain a composite precursor solution;
[0055] S2, add ammonia water to the composite precursor solution of S1 until the pH of the solution is about 9.5, continue stirring the reaction time for 2.5 hours, let it stand for 3.5 hours, filter it with suction, wash it with ethanol and deionized water once each, and dry it at 110°C for 2 hours to obtain a carrier intermediate product;
[0056] S3, then the carrier intermediate product was calcined at 500 ° C for 3 h in a nitrogen atmosphere, crushed and sieved to obtain MgO-Al 2 O 3 Composite carrier.
[0057] Example 3
[0058] 1) Accurately weigh 4 g of copper acetate and 10 g of cerium chloride and dissolve them in 100 ml of deionized water. After 1.5 h of magnetic stirring in a constant temperature water bath at 80° C., a transparent solution is obtained. Concentrated ammonia (25-28 wt.%) is added as a precipitant in sequence until the pH of the solution is greater than 8.0 to completely precipitate the metal ions. The solution is continuously magnetically stirred for 2 h in a constant temperature water bath at 90° C., and then aged and allowed to stand in a constant temperature water bath at 80° C. for 2.5 h to obtain a precipitated suspension;
[0059] 2) The precipitate suspension of step 1) is vacuum filtered, and the solid product is washed with deionized water until the total soluble solid TDS in the filtrate is <20ppm; the precipitate is transferred to an oven and dried at 100°C for 5h to obtain a copper-cerium solid powder precursor.
[0060] 3) Dissolve 1 g of nickel nitrate in an appropriate amount of deionized water, and add the nickel nitrate aqueous solution dropwise to the copper-cerium solid powder in step 2) until it is completely absorbed, then transfer to an oven and dry at 105° C. for 3 h to obtain a catalyst precursor.
[0061] 4) Take a certain amount of the above catalyst precursor, mix it with the composite carrier in a mass ratio of 1:1.2, and then transfer it into a tank and ball mill it for 2 hours to obtain a ball milled product.
[0062] 5) The product after ball milling in step 4) is calcined at 400° C. for 2 h, and then pressed into graphite to obtain a finished catalyst.
[0063] The preparation method of the composite carrier in this embodiment includes:
[0064] S1. Weigh 25 g of magnesium acetate and aluminum isopropoxide, dissolve them in 250 mL of deionized water, stir for 15 min, add 3.5 g of sodium polystyrene sulfonate, and stir and mix at 40 °C for 20 min to obtain a composite precursor solution.
[0065] S2, add ammonia water to the composite precursor solution of S1 until the pH of the solution is about 9.5, continue stirring the reaction time for 2.5 hours, let it stand for 3.5 hours, filter it with suction, wash it with deionized water twice, and dry it at 110°C for 2 hours to obtain a carrier intermediate product;
[0066] S3, then the carrier intermediate product was calcined at 600 ° C for 2 h in a nitrogen atmosphere, crushed and sieved to obtain MgO-Al 2 O 3 Composite carrier.
[0067] Example 4
[0068] 1) Accurately weigh 5 g of copper nitrate and 15 g of cerium chloride and dissolve them in 100 ml of deionized water. After 1.5 h of magnetic stirring in a constant temperature water bath at 80° C., a transparent solution is obtained. Concentrated ammonia (25-28 wt.%) is added as a precipitant in sequence until the pH of the solution is greater than 8.0 to completely precipitate the metal ions. The solution is continuously magnetically stirred for 2 h in a constant temperature water bath at 90° C., and then aged and allowed to stand for 2.5 h in a constant temperature water bath at 80° C. to obtain a precipitated suspension;
[0069] 2) The precipitate suspension of step 1) is vacuum filtered, and the solid product is washed with deionized water until the total soluble solid TDS in the filtrate is less than 20 ppm. The precipitate is transferred to an oven and dried at 100° C. for 5 h to obtain a copper-cerium solid powder precursor.
[0070] 3) Dissolve 1 g of cobalt nitrate in an appropriate amount of deionized water, and drop the aqueous cobalt nitrate solution into the copper cerium solid powder in step 2) until it is completely absorbed, then transfer to an oven and dry at 105° C. for 3 h to obtain a catalyst precursor.
[0071] 4) Take a certain amount of the above catalyst precursor, mix it with the composite carrier in a mass ratio of 1:1.2, and then transfer it into a tank and ball mill it for 2 hours to obtain a ball milled product.
[0072] 5) The product after ball milling in step 4) is calcined at 300° C. for 3 h, and then pressed into a sheet with graphite to obtain a finished catalyst.
[0073] The preparation method of the composite carrier in this embodiment includes:
[0074] S1. Weigh 25 g of magnesium acetate and aluminum isopropoxide, dissolve them in 250 mL of deionized water, stir for 15 min, add 3 g of lignin sulfonate, stir and mix at 50 °C for 10 min, and obtain a composite precursor solution.
[0075] S2, adding ammonia water to the composite precursor solution of S1 until the pH of the solution is about 10, continuing the stirring reaction time for 1.5 hours, standing for 2.5 hours, filtering, washing with anhydrous ethanol three times, and drying at 100°C for 2.5 hours to obtain a carrier intermediate product;
[0076] S3, then the carrier intermediate product was calcined at 700 ° C for 2 h in a nitrogen atmosphere, crushed and sieved to obtain MgO-Al 2 O 3 Composite carrier.
[0077] Example 5
[0078] The difference from Example 1 is that the lanthanum nitrate in step 3) is replaced by ruthenium nitrate, and the rest is the same as Example 1.
[0079] Example 6
[0080] The difference from Example 1 is that the lanthanum nitrate in step 3) is replaced by samarium nitrate, and the rest is the same as Example 1.
[0081] Example 7
[0082] The difference from Example 1 is that the lanthanum nitrate in step 3) is replaced by palladium nitrate, and the others are the same as Example 1.
[0083] Example 8
[0084] The difference from Example 1 is that the lanthanum nitrate in step 3) is replaced by lanthanum chloride, and the others are the same as Example 1.
[0085] Example 9
[0086] The difference from Example 1 is that the lanthanum nitrate in step 3) is replaced by samarium chloride, and the rest is the same as Example 1.
[0087] Example 10
[0088] The difference from Example 1 is that the lanthanum nitrate in step 3) is replaced by nickel chloride, and the rest is the same as Example 1.
[0089] Embodiment 11
[0090] The difference from Example 1 is that: in step 4), the catalyst precursor and the composite carrier are mixed in a mass ratio of 1:1.5, and the rest is the same as Example 1.
[0091] Example 12
[0092] The difference from Example 1 is that the precipitant in step 1) is sodium hydroxide, and the rest is the same as Example 1.
[0093] Embodiment 13
[0094] The difference from Example 1 is that the precipitant in step 1) is sodium carbonate, and the rest is the same as Example 1.
[0095] Embodiment 14
[0096] The difference from Example 1 is that the carrier S3 is calcined at 600°C for 4h, and the rest is the same as Example 1.
[0097] Embodiment 15
[0098] The difference from Example 1 is that the prepared carrier S3 is calcined at 700° C. for 4 h, and the rest is the same as Example 1.
[0099] Example 16
[0100] The difference from Example 1 is that in step 5), the calcination is carried out at 350° C. for 4 h, and the rest is the same as Example 1.
[0101] Embodiment 17
[0102] The difference from Example 1 is that in step S3 of the carrier preparation process, calcination is carried out in air, and the rest is the same as Example 1.
[0103] Comparative Example 1
[0104] The difference from Example 1 is that in step 1), cerium nitrate is not used, and an equal amount of copper nitrate is used instead of cerium nitrate, and the rest is the same as Example 1.
[0105] Comparative Example 2
[0106] The difference from Example 1 is that the modifier is omitted and step 3) is not performed. The rest is the same as Example 1.
[0107] Comparative Example 3
[0108] The difference from Example 1 is that after the catalyst precursor is mixed with the composite carrier, calcination is directly performed, and the ball milling process is omitted. The rest is the same as Example 1.
[0109] Comparative Example 4
[0110] The difference from Example 1 is that the composite carrier in step 4) is replaced by an equal amount of magnesium oxide carrier, and the rest is the same as Example 1.
[0111] Comparative Example 5
[0112] The difference from Example 1 is that the composite carrier in step 4) is replaced by an equal amount of alumina carrier, and the rest is the same as Example 1.
[0113] Comparative Example 6
[0114] The difference from Example 1 is that polyvinyl alcohol is omitted in S1 for preparing the composite carrier, and the rest is the same as Example 1.
[0115] Comparative Example 7
[0116] The difference from Example 1 is that in S1 for preparing the composite carrier, an equal amount of sodium dodecyl sulfate is used instead of polyvinyl alcohol, and the rest is the same as Example 1.
[0117] Comparative Example 8
[0118] The difference from Example 1 is that in step S3 of preparing the composite carrier, calcination is performed at 900° C. for 4 h, and the rest is the same as Example 1.
[0119] Comparative Example 9
[0120] The difference from Example 1 is that in step S3 of preparing the composite carrier, calcination is performed at 300° C. for 4 h, and the rest is the same as Example 1.
[0121] The performance of the catalysts prepared in the examples and comparative examples in the methanol steam reforming hydrogen production process was tested: the performance of the prepared catalysts was tested according to the following catalyst performance testing method, and the test results are shown in Table 1.
[0122] 1. Test method: The catalyst performance test is carried out on a 10ml continuous flow fixed bed. 0.2g of catalyst is loaded into the reactor, and the temperature is directly raised to the reaction temperature under a nitrogen atmosphere. The ventilation is stopped, and a double-plunger micropump is used to transport methanol and aqueous solution. The raw materials are preheated and enter the reactor for reaction. After the reaction starts, the gas phase and liquid phase products are analyzed to obtain the methanol conversion rate and CO selectivity.
[0123] 2. The hydrogen production rate is calculated by the water displacement method to obtain the gas production volume. The hydrogen production rate is the μmol hydrogen content produced per gram of catalyst per second.
[0124] 3. Thermal stability test: The catalyst was heated to 813K under reaction conditions and then cooled to 423K for 15 hours. The thermal stability was evaluated by comparing the activity before and after the heat treatment.
[0125] Catalyst reaction conditions: reaction temperature 250°C, mass space velocity 2.69h -1 , reaction pressure normal pressure, H 2 O / CH 3 OH=1.2 (molar ratio).
[0126] Table 1. Comparison of catalyst performances prepared in different embodiments
[0127]
[0128]
[0129] According to the results in Table 1, the hydrogen production rate of the catalysts in Examples 1-17 is greater than 70 mol·g cat -1 ·s -1 ; The conversion rate of methanol is greater than 94%; The selectivity of CO is less than 0.26%; The thermal activity retention rate is greater than 96%. It can be seen that the methanol reforming hydrogen production catalyst provided by the embodiment of the present invention has excellent hydrogen production rate, high methanol conversion rate, good CO selectivity, and good catalyst stability.
[0130] Comparison of Example 1 with Comparative Example 1 shows that the catalyst product of Example 1 has better hydrogen production rate and stability, and a high methanol conversion rate. 2 In the crystal lattice, the growth of copper grains is inhibited during use, preventing the catalyst from sintering and deactivation, thereby increasing the hydrogen production rate and improving stability.
[0131] Compared with Example 1, after the lanthanum nitrate modifier was omitted in Comparative Example 2, the hydrogen production rate, methanol conversion rate, CO selectivity and stability of the catalyst were significantly reduced; Comparative Example 3 did not perform ball milling, which was not conducive to the combination of the active components of the catalyst with the carrier, and the stability performance was significantly reduced.
[0132] Compared with Example 1, Comparative Examples 4-5 used magnesium oxide and aluminum oxide in the prior art as catalyst carriers, which had poor binding properties with the active components of the catalyst, and thus the hydrogen production rate, methanol conversion rate, CO selectivity and stability were lower than those of the composite carrier used in Example 1.
[0133] Compared with Example 1, Comparative Example 6 does not use a polymer surfactant, and Comparative Example 7 uses sodium dodecyl sulfate in a non-polymer surfactant instead of polyvinyl alcohol. The polymer surfactant in Example 1 is conducive to adsorption on the surface of magnesium oxide or aluminum oxide, slowing down the aggregation of magnesium oxide or aluminum oxide, and is conducive to calcining to form MgO-Al with specific pores. 2 O 3The composite carrier has more stable performance and is beneficial to the loading of active components of the catalyst, thereby improving the hydrogen production rate, methanol conversion rate, CO selectivity and stability.
[0134] Compared with Example 1, the calcination temperature of the composite carrier prepared in Comparative Example 8 is too high, and the calcination temperature of the composite carrier prepared in Comparative Example 9 is too low. When the calcination temperature for preparing the composite carrier is too high, the magnesium oxide and aluminum oxide in the carrier are easy to agglomerate, which is not conducive to the combination of the catalyst active components and the composite carrier. When the calcination temperature is too low, a carrier with stable performance cannot be formed. Therefore, the catalysts prepared in Comparative Examples 8-9 have significantly reduced hydrogen production rate, methanol conversion rate, CO selectivity and stability.
[0135] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for preparing a reforming hydrogen production catalyst, characterized in that: The following steps are involved: 1) mixing copper salt, cerium salt and water uniformly, adding a precipitant until the pH value is greater than 8.0, heating and stirring, standing and aging to obtain a precipitate suspension; wherein the mass ratio of copper salt to cerium salt is 1-5:10-20; 2) washing and filtering the precipitated suspension in step 1) or centrifuging and washing it, and drying it to obtain a copper-cerium mixed precursor; 3) dissolving a modifier in water, impregnating the mixed precursor of step 2), and drying to obtain a catalyst precursor; the modifier is selected from chlorides or nitrates of metal ions such as Pt, Pd, Ru, La, Sm, Co, Ni, and Zr; the mass fraction of the modifier is 0.1% to 15% of the total mass of the copper salt and the cerium salt; 4) mixing the catalyst precursor of step 3) with the composite carrier in a mass ratio of 1:1-2, and then transferring the mixture into a tank for ball milling to obtain a ball milling product; 5) calcining the product after ball milling in step 4) at 250-500° C. for 1-5 h, and then adding graphite to form a sheet to obtain a finished catalyst; The preparation method of the composite carrier comprises the following steps: S1. Mix a magnesium source and an aluminum source in a mass ratio of 1:0.5-4, disperse them in water, add a polymer surfactant, and stir to obtain a mixed solution; the polymer surfactant comprises at least one of polyvinyl alcohol, polyacrylamide, sodium polystyrene sulfonate, and lignin sulfonate; the mass fraction of the polymer surfactant is 1-30% of the total amount of the magnesium source and the aluminum source; S2, adding ammonia water to the mixed solution of step S1 until the pH value of the solution is 9-10, continuing to stir the reaction for 1-3 hours, standing, filtering, washing, and drying to obtain a carrier intermediate product; S3. The carrier intermediate product of step S2 is calcined in nitrogen or air at 450-700° C. for 2-4 hours to obtain a MgO-Al2O3 composite carrier.
2. The method for preparing a reforming hydrogen production catalyst according to claim 1, characterized in that: In step 1), the copper salt includes at least one of copper nitrate, copper acetate and copper chloride; the cerium salt includes at least one of cerium nitrate and cerium chloride.
3. The method for preparing a reforming hydrogen production catalyst according to any one of claims 1 to 2, characterized in that: In step 1), the precipitant is at least one of ammonia water, sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate.
4. The method for preparing a reforming hydrogen production catalyst according to any one of claims 1 to 2, characterized in that: Step 1) The heating temperature is 50-80° C., the stirring time is 1-5 hours, and the standing aging time is 2-6 hours.
5. The method for preparing a reforming hydrogen production catalyst according to any one of claims 1 to 2, characterized in that: The ball milling includes dry ball milling or wet ball milling, and the ball milling time is 5 to 5 hours; the medium of the wet ball milling includes at least one of water, anhydrous ethanol, glycerol, and isopropanol.
6. The method for preparing a reforming hydrogen production catalyst according to any one of claims 1 to 2, characterized in that: In step S1 of preparing the composite carrier, the magnesium source includes at least one of magnesium chloride, magnesium nitrate, and magnesium acetate; the aluminum source includes at least one of aluminum chloride, aluminum nitrate, and aluminum isopropoxide.
7. The method for preparing a reforming hydrogen production catalyst according to any one of claims 1 to 2, characterized in that: In step S2 of preparing the composite carrier, the stirring reaction time is 1 to 3 hours; and the standing time is 2 to 5 hours.
8. The method for preparing a reforming hydrogen production catalyst according to any one of claims 1 to 2, characterized in that: In step S2 of preparing the composite carrier, distilled water and / or ethanol are used for washing, and the drying temperature is 90-110° C. for 1-4 hours.
9. A reforming hydrogen production catalyst obtained according to the preparation method according to any one of claims 1 to 8.
10. Use of the reforming hydrogen production catalyst as claimed in claim 9 in catalyzing methanol reforming to produce hydrogen, characterized in that: The reaction temperature of the reforming hydrogen production catalyst when catalyzing methanol reforming to produce hydrogen is 170-350°C.
Citation Information
Patent Citations
Copper-based catalyst for hydrogen production by methanol steam reforming and preparation method and application thereof
CN113731429A
Copper-based methanol steam reforming hydrogen production catalyst and preparation method thereof
CN114870859A
Catalyst for water vapor reformation of ethanol to prepare hydrogen and its preparing method and use
CN1986049A